Impact of estrogens and estrogen receptor-α in brain lipid metabolism - Morselli, Eugenia (Am J Physiol Endocrinol Metab, 2018)
Estrogens and their receptors play key roles in regulating body weight, energy expenditure, and metabolic homeostasis. It is known that lack of estrogens promotes increased food intake and induces the expansion of adipose tissues, for which much is known. An area of estrogenic research that has received less attention is the role of estrogens and their receptors in influencing intermediary lipid metabolism in organs such as the brain. In this review, we highlight the actions of estrogens and their receptors in regulating their impact on modulating fatty acid content, utilization, and oxidation through their direct impact on intracellular signaling cascades within the central nervous system.